Schwann cells in neuromuscular in vitro models - Hörner, Sarah J.; Couturier, Nathalie; Hafner, Mathias; Rudolf, Rüdiger (Biological chemistry, 2024)
Neuromuscular cell culture models are used to investigate synapse formation and function, as well as mechanisms of de-and regeneration in neuromuscular diseases. Recent developments including 3D culture technique and hiPSC technology have propelled their ability to complement insights from in vivo models. However, most cultures have not considered Schwann cells, the glial part of NMJs. In the following, a brief overview of different types of neuromuscular cocultures is provided alongside examples for studies that included Schwann cells. From these, findings concerning the effects of Schwann cells on those cultures are summarized and future lines of research are proposed.